Utilizing PAI Learning Assignment Strategy to Enhance Student Leadership Character at Ta'mirul Islamic Boarding School Surakarta - Amin Choiru Sholeh; Siti Rohimah (South Sulawesi Education Development (SSED), 2024)
Leadership is the ability to influence others through communication, with the goal of encouraging them to be willing to follow the leader's direction with understanding, awareness, and voluntarily. Indicators of Islamic leadership character in students include aspects of religion, discipline, implementation of pesantren programs and Islamic environment, as well as leadership spirit in student council. One way of teaching that can be used by teachers in the learning process is through the assignment method. The application of this method can help prove the leadership abilities possessed by students. Pondok Pesantren Ta'mirul Islam Surakarta, as an Islamic educational institution, faces a series of problems in developing student leadership character through assignment strategies. The respondents who will be the focus of this study are 5 students and 1 administrator. Data collection techniques in qualitative research at Ta'mirul Islam Islamic Boarding School Surakarta use interviews, observations, and documentation. In this study, researchers used interactive analysis of the Miles and Huberman model. The implementation of the assignment strategy at Ta'mirul Islam Islamic Boarding School Surakarta has created an environment that supports the development of strong character and leadership among students. Researchers obtained the results of two important aspects, regarding leadership assignments in Ponpes can contribute in helping students develop an understanding of Islamic values and leadership character development occurs in the context of assignment strategies at Ta'mirul Islam Islamic Boarding School Surakarta. Based on the results of the study, it can be concluded that the PAI learning assignment strategy has a significant impact in strengthening the leadership character of students at the Ta'mirul Islam Islamic Boarding School Surakarta.